(untitled) (Journal of Computational Mathematics, 2021)
In a composite-step approach, a step s_k is computed as the sum of two components v_k and h_k. The normal component v_k, which is called the vertical step, aims to improve the linearized feasibility, while the tangential compoent h_k, which is also called horizontal step, concentrates on reducing a model of the merit functions. As a filter method, it reduces both the infeasibility and the objective function. This is the same property of these two methods. In this paper, one concerns the composite-step like filter approach. That is, a step is tangential component h_k if the infeasibility is reduced. Or else, s_k is a composite step composed of normal component v_k and tangential component h_k.